Search for supersymmetry using final states with one lepton, jets, and missing transverse momentum with the ATLAS detector in √s = 7 TeV pp collisions - Anduaga, Xabier Sebastián (2011)
This Letter presents the first search for supersymmetry in final states containing one isolated electron or muon, jets, and missing transverse momentum from √s = 7TeV proton-proton collisions at the LHC. The data were recorded by the ATLAS experiment during 2010 and correspond to a total integrated luminosity of 35pb-1. No excess above the standard model background expectation is observed. Limits are set on the parameters of the minimal supergravity framework, extending previous limits. Within this framework, for A0 = 0 GeV, tan-β=3, and μ>0 and for equal squark and gluino masses, gluino masses below 700 -GeV are excluded at 95% confidence level.